Megaloblastic Anemia at the Hospital Nacional Daniel A. Carrión 1989-1994 - Díaz Hayashida, Doris (1997)
A review of the cases diagnosed as having megaloblastic anemia (n=70), in the last five years at the Hospital Nacional Daniel A. Carrion, is presented. Results: We found the following clinical diagnosis: pallor (80%), apathy (60%), diarrhea (51%), dyspnea (48.4%), weight loss (34.2%), epigastralgia (28%), edema and/or ascitis (22.8%), and neurological symptoms (11.4%). Among the associated entities, there were diseases of the upper gastrointestinal tract (51.4% of which were demonstrated endoscopically); alcoholism was present in 25.7%, whereas in 14.2% of cases there was no another concomitant disease. All of our patients developed anemia with a low reticulocite count, and had Marrow Production Index (MPI) values 1.0. 88.57% of patients had MPI values lower than 0,5 and 43% had MPI values between 0.6 and 0.9. Most of patients showed pancytopenia (45.78%), whereas 42.78% of cases had decreased counts of two cellular lines, and 11.44% of cases had only erythropenia. For the most of patients (42.84%), hematocrit values ranged to 21 - 25%; hematocrit values lower than 15% was seen in 31.43% of patients and there were not patients which exceeds a hematocrit value of 30%. Iron storages at the marrow were normal in 53% of cases, and they were increased in 25%; whereas in 22% of patients, there were decreased or absent amounts of iron. Ten of our patients developed jaundice, 70% of them had total bilirrubin levels between 1,2 - 2,5, and 30% had bilirrubin levels 2.6. We can conclude, from our observations and from the lack of national records, that there are a increasing number of patients with Megaloblastic Anemia in Callao. The most prevailing clinical picture consist of gastrointestinal symptoms, and its cause remain unknown.